Living in the end times. - Žižek, Slavoj (London : Verso, 2010)
The spiritual wickedness in the heavens ## Denial : the liberal utopia. Hollywood today : report from an ideological battlefield ## Anger : the actuality of the theologico-political. Reverberations of the crisis in a multi-centric world ## Bargaining : the return of the critique of political economy. The architectural parallax ## Depression : the neuronal trauma, or, the rise of the proletarian cogito. Apocalypse at the gates ## Acceptance : the cause regained.
Onderzoek KASK Professioneel (OFVP)
boek